Perceptions of Elementary School Teacher in Artificial Intelligence for Learning: Perspective of Theory of Planner Behaviour - Maigina, Ain; Fathurrohman; Wuri Wuryandani (International Journal of Elementary Education, 2024)
The development of technology and the ease of using artificial intelligence in educational activities are things that must be adjusted to the conditions of practitioners in the field. This study aims to determine the perceptions of elementary school teachers about the use of artificial intelligence in learning. The study was conducted using a qualitative descriptive method on 75 elementary school teachers in Purworejo Regency. Data collection was carried out using a closed questionnaire and Focus Group Discussion (FGD). Data analysis used a descriptive quantitative approach. The results of the findings showed that the highest factor was control beliefs, namely the aspect of teacher self-efficacy towards the use of AI, but teachers were also aware of the lack of digital competence they had. The six aspects that are indicators of the three TPB factors are at high values so that it is known that there is a positive intention of teachers regarding the use of AI in learning. However, it is also known that there is a contradiction, namely the high belief of teachers in the use of AI but the existence of digital competence, especially in the use of AI that has not been maximized. The aspect of basic knowledge that represents behavioural beliefs needs more intensive attention from related parties and further researchers.